DR-MELD: A New Concept to Predict Graft Survival after Liver Transplantation with Aged Donors. (July 2018) - Maestro, Oscar Caso; Alonso, Iago Justo; Muñoz, Carlos; Quinto, Alberto Marcacuzco; Garcia-Conde, Maria; Pulido, Jorge Calvo; Molero, Felix Cambra; Municio, Alejandro Manrique; Del Pozo Elso, Pilar; Sesma, Alvaro Garcia; Nutu, Anisa; Romero, Carlos Jimenez
Abstract : Introduction: The use of old grafts is one of the main sources to increase the number of available grafts for liver transplantation (LT). D-MELD seems to be the best graft survival predictor to date, but if we combine D-MELD with other variables maybe we can get a better score to predict survival. The aim of this study is analyse our experience in LT with donors >70 years, identify independent predictors of graft survival, and then, try to combine these predictors in an attempt to find a new score to predict graft survival. Materials and Methods: We present a longitudinal and retrospective study of all LT performed in our department using grafts >70 years. Donor, recipient, LT complications, and short, medium and long-term follow-up variables were analyzed. Results: From April 1986 to May 2016, 1848 LT were performed in 1659 patients. We performed 232 LT with grafts from donors >70 years, 20 cases were excluded, so 212 cases were included in the analysis. Donor median age was 76 years and 125 (59%) donors were females. We found hypertension in 122 (57, 5%) donors and diabetes in 43 (20, 3%). A biopsy was taken from all grafts during the procurement process, diffuse microsteatosis was described in 41 (19, 5%) patients and mild steatosis in 56 (26, 7%). Recipient median age was 59 years and 167 (78, 8%) patients were males. The indication for LT was alcohol in 95 (44, 8%) patients and HCV in 72 (34%) patients. Hepatocellular carcinoma (HCC) was diagnosed in 84 (39, 3%) patients. Median recipient MELD score was 13 and median recipient D-MELD was 1051. Mean CIT was 445 minutes. After a mean follow-up of 64 months, PNF was present in 3, 3%, acute rejection in 25%, vascular complications, in 6, 6% biliary complications in 7, 5% and liver re-transplantation was necessary in 12 (5, 7%) patients. Finally, patient and graft survival at 5 years was 69% and 64.5%, respectively. In the multivariate analysis we identified as independent risk factors for a worse graft survival HCV, donor age, recipient age and D-MELD. Searching a new score to predict old livers surival, we multiply the D-MELD value and the recipient age (DR-MELD) and we applied the Kaplan-Meier method with the Log-Rank test to study the influence of this parameter on the graft survival. Mean DR-MELD value was 50.286 (range 4752-234.000). Graft survival at 5 years was 100% for DR-MELD <25.000, 76, 2% for DR-MELD 25.000-50.000, 767, 8% for DR-MELD 50.000-75.000, 52, 1% for DR-MELD 75.000-100.000 and 49% for DR-MELD >100.000 (p<0, 00). Conclusion: DR-MELD seems to be a good predictor of graft survival after LT with donors >70 years and very easy to use in daily clinical practice.